2005
DOI: 10.1063/1.1941455
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of 0.5 nm thick Hf-silicate top-layer∕HfO2 gate dielectrics by atomic layer deposition

Abstract: The electrical properties have been studied for hafnium (Hf)-based gate stack structures, fabricated using atomic layer deposition (ALD) technology. The very thin ALD Hf-silicate layers on the top of HfO2 gate structures were very important in obtaining good electrical properties, because these surface films prevented a reaction between the polysilicon electrodes and HfO2 films during high temperature activation annealing. From subthreshold characteristic measurements, Ioff values were less than about 10pA∕μm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…Currently, sputtering and or metal organic chemical vapor deposition methods are used for the high-k film formation [3][4][5][6][7][8][9]. Furthermore, the very thin Hf-silicate layers on the top of HfO 2 gate structures are very important in obtaining good electrical properties, because these surface films prevent a reaction between the poly-silicon electrodes and HfO 2 films during high temperature activation annealing [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, sputtering and or metal organic chemical vapor deposition methods are used for the high-k film formation [3][4][5][6][7][8][9]. Furthermore, the very thin Hf-silicate layers on the top of HfO 2 gate structures are very important in obtaining good electrical properties, because these surface films prevent a reaction between the poly-silicon electrodes and HfO 2 films during high temperature activation annealing [10].…”
Section: Introductionmentioning
confidence: 99%
“…Hafnium-tetrachloride (HfCl 4 ) and water (H 2 O) have been widely used for depositing HfO 2 using ALD [11][12][13][14]. Recently, there have been reports of using Hf amide type precursors such as Hf(N(CH 3 )(C 2 H 5 )) 4 for HfO 2 or Hf-aluminate to overcome problems such as the excessive particles or residual chlorine obtained when using HfCl 4 precursors [10,14,15,20]. Furthermore, ALD HfO 2 films have been deposited at low temperatures (around 300°C), using a Hf(N(CH 3 )(C 2 H 5 )) 4 precursor and O 3 instead of H 2 O as the oxidant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 However, it has been reported that Hf and Zr silicate systems can decompose into SiO 2 and metal oxide at temperature annealing above ϳ800°C due to the positive enthalpy of mixing of SiO 2 and metal oxides. 5 These phase separations lead to the degradation of thermal stability, dielectric and electrical properties.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8] Another possible deposition technique is atomic layer deposition ͑ALD͒, which has some desirable features in that it allows precise control of composition, film thickness, conformality, and uniformity. [9][10][11][12][13][14][15] Hafnium tetrachloride ͑HfCl 4 ͒ and water ͑H 2 O͒ have been widely used to deposit HfO 2 using the ALD technique. 9,10 There have been reports of groups using Hf-amide-type precursors such as Hf͓N͑CH 3 ͒͑C 2 H 5 ͔͒ 4 for growing HfO 2 or Hf-aluminate films in order to solve the problem of particles that occurs when using HfCl 4 precursors.…”
mentioning
confidence: 99%